Mature Teratoma of the Mediastinum in an Adolescent: Clinical Camouflage as Meningioma with Hemoptysis and Pleural Effusion - Adi Astron Prasetio; Darmawan Ismail (Open Access Indonesian Journal of Medical Reviews, 2025)
Mediastinal mature teratomas are relatively common germ cell tumors in adolescents, typically located in the anterior mediastinum. While often benign and slow-growing, they can cause symptoms like hemoptysis through compression or local invasion. The differential diagnosis can rarely include ectopic meningioma, posing significant diagnostic challenges. The aim of this report is to describe this unusual presentation of a mediastinal mature teratoma and to emphasize the importance of a comprehensive, multidisciplinary diagnostic workup for achieving an accurate diagnosis and guiding appropriate management in such complex cases of mediastinal pathology. A 17-year-old female presented with a two-month history of blood-streaked hemoptysis and intermittent central chest pain. She had no systemic symptoms such as fever or weight loss. Physical examination was largely unremarkable, though laboratory tests revealed mild anemia (Hb 9.2 g/dL). Imaging studies, including chest X-ray and contrast-enhanced thoracic multi-slice computed tomography (MSCT), identified a large, heterogeneous anterior to middle mediastinal mass. The mass was noted to compress the right main bronchus, causing right lower lobe atelectasis, and was associated with minimal right-sided pleural effusion and mediastinal lymphadenopathy. The MSCT findings were suggestive of a teratoma. A core biopsy of the mediastinal mass indicated a mature teratoma but also raised meningioma as a differential diagnosis. Bronchoscopy revealed mucosal hyperemia and hypervascularity in the tracheobronchial tree. A brain MRI was negative for intracranial metastasis. The patient was managed conservatively pending further comprehensive evaluation and multidisciplinary team discussion. In conclusion, this case underscores an atypical presentation of a mediastinal mature teratoma in an adolescent, characterized by hemoptysis, pleural effusion, and a rare histopathological differential of meningioma. It highlights the critical role of meticulous and comprehensive diagnostic evaluation, including advanced imaging and histopathology, along with a multidisciplinary approach, in accurately diagnosing and planning the management of such complex mediastinal masses, especially when faced with unusual clinical or pathological features.